Avverbi posizionali in italiano: Deissi orientata al parlante e al territorio - Bernini, Giuliano (Verbum – Analecta Neolatina, 2025)
On the basis of the KIParla corpus, a survey is made of the use of positional adverbs forming complex prepositional phrases that anchor the situation described in a sentence in a deictic reference field oriented towards a territorial conceptualization. Positional function is performed by deictic locative adverbs with the speaker as orīgo and by the adverbs su ‘up’ and giù ‘down’ along a vertical dimension to which the speaker associates the situation described in the sentence on the basis of a point of view. This can be given in the discourse, pragmatically implied or considered shared with respect to the territory being spoken about with reference to its morphology or to the geographical continuum between the north and south poles. It is not possible to determine whether in the use of positional adverbs greater specific weight can be attributed to the discourse conditions or the speakers’ regional varieties with a dialectal substratum with ground-oriented deixis systems.